Evaluasi Usability Dan Perbaikan Desain Antarmuka Pengguna Aplikasi MejaKita Menggunakan Metode Goal-Directed Design (GDD) - Rezza Ananda Yoanko; Retno Indah Rokhmawati; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
MejaKita is an online-based learning media specifically designed as a space for students in Indonesia to share knowledge and learn together. The usability on this application was evaluated to find out how far the system works, to see the effect of interface design from users, and to identify the obstacles in the system. The evaluation was directed to 10 categorized respondents as potential users of the application. The usability evaluation of MejaKita application was about to measure 3 aspects of usability as effectiveness, efficiency, and satisfaction, by using those methods such as completion rate, overall relative efficiency, and the system usability scale questionnaire. After first evaluation, turned out the problem was needs of improvement on the application design to figured out whether the planned draft meets the user needs. MejaKita uses Goal-Directed Design as method to create a design improvement that meets user needs and to get validation from the first plan by developer when the application was made. The results of final evaluation scored 91,4% and 78,9% as two aspects increased 35,7% and 35,2% in total. The outcome of system usability scale of satisfaction aspect scored 77,75 which increased 30,25 from last evaluation and get acceptable category scored B+.